Can geometric indices of heart rate variability predict improvement in autonomic modulation after resistance training in chronic obstructive pulmonary disease? - Santos, Ana Alice Soares dos [UNESP]; Ricci-Vitor, Ana Laura [UNESP]; Bragatto, Vanessa Santa Rosa [UNESP]; Santos, Ana Paula Soares dos [UNESP]; Ramos, Ercy Mara Cipulo [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP] (Wiley-Blackwell, 2015)
Chronic obstructive pulmonary disease (COPD) is associated with autonomic dysfunctions that can be evaluated through heart rate variability (HRV). Resistance training promotes improvement in autonomic modulation; however, studies that evaluate this scenario using geometric indices, which include nonlinear evaluation, thus providing more accurate information for physiological interpretation of HRV, are unknown. This study aimed to investigate the influence of resistance training on autonomic modulation, using geometric indices of HRV, and peripheral muscle strength in individuals with COPD. Fourteen volunteers with COPD were submitted to resistance training consisting of 24 sessions lasting 60 min each, with a frequency of three times a week. The intensity was determined as 60% of one maximum repetition and was progressively increased until 80% for the upper and lower limbs. The HRV and dynamometry were performed at two moments, the beginning and the end of the experimental protocol. Significant increases were observed in the RRtri (4·81 ± 1·60 versus 6·55 ± 2·69, P = 0·033), TINN (65·36 ± 35·49 versus 101·07 ± 63·34, P = 0·028), SD1 (7·48 ± 3·17 versus 11·04 ± 6·45, P = 0·038) and SD2 (22·30 ± 8·56 versus 32·92 ± 18·78, P = 0·022) indices after the resistance training. Visual analysis of the Poincare plot demonstrated greater dispersion beat-to-beat and in the long-term interval between consecutive heart beats. Regarding muscle strength, there was a significant increase in the shoulder abduction and knee flexion. In conclusion, geometric indices of HRV can predict improvement in autonomic modulation after resistance training in individuals with COPD; improvement in peripheral muscle strength in patients with COPD was also observed.
Keywords: Autonomic nervous system; Exercise; Heart rate; Muscle strength; Nonlinear dynamics; Respiratory tract diseases